2019
DOI: 10.2139/ssrn.3422155
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of MiFID II on Sell-Side Analysts, Buy-Side Analysts, and Firms

Abstract: Nimé for excellent research assistance. We are grateful to Drago Sab u, Java software developer, for the application that extracts the conference call participants, and to FactSet for providing the conference call transcripts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(59 citation statements)
references
References 29 publications
9
50
0
Order By: Relevance
“…First, we provide evidence about MiFID II, an economically significant reform, contributing to the emerging academic literature as well as providing practical implications. Our paper complements Fang et al (2020), Guo andMota (2021), andLang et al (2021)-which show that MiFID II impacts capital markets through changes in analyst behavior-by focusing firms rather than analysts and how firms' voluntary disclosure also play a role in the new environment. More specifically, our paper shows that managerial guidance can be a major source of information for investors while the informational value of sell-side research may decline in the post-MiFID II period.…”
Section: Introductionmentioning
confidence: 53%
See 4 more Smart Citations
“…First, we provide evidence about MiFID II, an economically significant reform, contributing to the emerging academic literature as well as providing practical implications. Our paper complements Fang et al (2020), Guo andMota (2021), andLang et al (2021)-which show that MiFID II impacts capital markets through changes in analyst behavior-by focusing firms rather than analysts and how firms' voluntary disclosure also play a role in the new environment. More specifically, our paper shows that managerial guidance can be a major source of information for investors while the informational value of sell-side research may decline in the post-MiFID II period.…”
Section: Introductionmentioning
confidence: 53%
“…For example, the UK's Financial Conduct Authority finds that the unbundling provision enhanced buy-side firms' accountability and scrutiny over research costs without sacrificing their access to research, resulting in an overall benefit for investors (Financial Conduct Authority, 2019). This accountability and scrutiny over research costs introduced competition to sell-side research, and academic studies have indeed identified positive outcomes of this increased competition-improved quality of sell-side analyst forecasts, most notably enhanced analyst forecast accuracy (Fang et al, 2020;Guo and Mota, 2021;Lang et al, 2021). In addition, Fang et al (2020) find that stock recommendations become more informative and analyst reports are more likely to contain industry recommendations.…”
Section: Background and Hypothesis Developmentmentioning
confidence: 99%
See 3 more Smart Citations